Karo Ethnic Experience in Seeking Health Services to Penang Malaysia - Sri Mayanti Sirait; Destanul Aulia; Nurman Achmad (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Regency in North Sumatra Province has 213 hospital units consisting of 187 general hospitals and 26 specialized hospitals, although there are many health services but many seek treatment abroad, such as to Penang, Malaysia. In 2015 there were 600,000 patients taking treatment to Penang. The amount of government foreign exchange issued to foreign hospitals is as much as 600 million dollars in one year, if this is not immediately handled it will have a negative impact on the country's economy. The purpose of this study is to explore the experience of Karo Ethnics who seek treatment in Penang. This type of research is a qualitative research with a phenomenological approach. Participants numbered eight people. The themes found in this study are three, namely (1) getting a financial comparison, (2) choosing health services, (3) getting satisfying health services. In conclusion, participants had less than satisfactory experiences, so Karo Ethnics tried to find and choose satisfying health services. It is recommended to health services in Indonesia to improve health services to the community.